Palmeras comunes del bosque ribereño del Lago Valencia (Madre de Dios, Perú): usos, semillas y propagación - Ramos-Huapaya, Andrea E. (2024)
The Madre de Dios region, considered the biodiversity capital of Peru, is home to a great diversity of palms. However, there are few studies on the palm common in riparian forest. In this sense, it is essential to carry out projects and initiatives that describe the palm, their uses, their seeds and their propagation, in order to know, conserve and sustainably manage this resource. Therefore, the objective of this research was to identify part of the diversity of common palm in Madre de Dios, in order to encourage to conservation of riparian forests, taking reference to the riparian forest of Valencia Lake (Las Piedras district, Tambopata, Madre de Dios). The research was carried out at the Valencia Station of the NGO Inkaterra Asociation, identifying 10 species of common palm by collecting fruits and processing seeds. It is recommended to continue with projects to learn about and identify the natural resources of forest ecosystems such as riparian forests, as well strategies for fruit collection and seed processing. It is also suggested that studies by conducted on the biology and ecology of forest seeds and palm seeds, the chemical characterization of the edible parts of palms, and complementary phenology studies to understand the possible effect of climate change on the life cycle of plants.